Detection of Microbiological Activity in Some Collected Water Samples near Dumping Site of Solid Waste, Khartoum North, Sudan - Elamin Abbass , Omer Abbass; Elhassan , Abdelelah Mohamed; Abdelgadir , Abdelgadir Elfadil; Mohamed , Mariam Hamdan (Tropical Aquatic and Soil Pollution, 2023)
A study was conducted at the Wadafiea landfill in Al Khartoum Bahri (North), Sudan, to determine the level of microbial contamination in water samples collected from nearby areas around the landfill. The purpose of this study was to evaluate the impact of solid waste disposal in open dumps and assess the associated risks to water. The study tested for coliform bacteria (E.coli) and compared the seasonal differences between the samples collected during the dry and rainy seasons. The results indicated higher levels of E.coli contamination in each season, with the rainy season samples showing particularly high levels (66.03 × 10⁴ cfu/ml) compared to the dry season (31.93 × 10⁴ cfu/ml). It was concluded that the groundwater was highly polluted due to the current landfill location. The local authorities and the department of solid waste management were advised to close this landfill and relocate it to the outskirts of Al Khartoum Bahri (North) city. Additionally, it was recommended that international regulations for standard landfills should be maintained and implemented.